Analysis Of Students' Cognitive Process Through Minimum Competency Assessment Mathematics Question in Grade 8^th in Junior High School - Laelasari, L; Utami, Tia (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to analyze students' cognitive processes through minimum competency assessment questions. This study uses a qualitative research approach with a descriptive method to describe the mental process of students using minimum competency assessment questions that are carried out at the beginning of learning. The results showed that 13 out of 22 students could use previous knowledge and explain how they used it to understand the text, 21 could identify important and relevant ideas, and as many as 9 students were able to make realistic inferences and cite supporting evidence. Most students cannot yet think mathematically and can solve the given problems. This study also found that as many as 19 students were able to define all vocabulary and be able to explain it. Eighteen participants could not understand the multimodal text, and showed that 11 students were quite able to show how to understand the text even though it was incomplete. Teachers can use this data for initial data as a reference for implementing learning strategies for future teaching.